Distinct cytokine-producing dendritic cell profiles in females and males with major depressive disorder - Boller, Anna-Lena; Freff, Jana; Bast, Maximilian; Schwarte, Kathrin; Dannlowski, Udo; Baune, Bernhard T.; Scheu, Stefanie; Alferink, Judith (Frontiers in Cellular Neuroscience, 2026)
IntroductionMajor depressive disorder (MDD) is a revalent and disabling condition increasingly associated with immune dysregulation. Dendritic cells (DCs) are key immune sentinels that shape inflammatory responses and T-cell polarization, including Th17 pathways implicated in depression-related mild inflammation. Given well-documented sex differences in immune responses and cytokine profiles in MDD, differential DC activation may represent a mechanistic link between sex-associated immune cell profiles in depression. However, DCs remain insufficiently characterized in MDD.MethodsWe performed an exploratory study using flow cytometry-based immunophenotyping to assess circulating DC subsets, including CD1c+ and CD141+ conventional DCs (cDCs), plasmacytoid DCs (pDCs), and their cytokine profiles in individuals with MDD (n = 55) and healthy controls (HC, n = 32). Stratification by depression severity and sex, together with correlation and multivariate linear regression analyses, and cluster analysis, was used to examine associations between DC subsets and depressive symptom severity in females and males.ResultsStratification by HAM-D17 scores revealed reduced counts of pDCs and increased frequencies of CD11c+ cDCs in the peripheral blood (PB) of severely depressed participants compared to HC or mildly depressed patients, respectively. Regarding cytokine-producing DCs, sex-stratified analyses showed that frequencies of IL-23+ cDCs were elevated and symptom-associated only in females with MDD compared to sex-matched controls, whereas frequencies of TNF+, IL-1β+, and IL-6+ cDCs were selectively increased in depressed males. Cluster analyses identified distinct female- and male-specific DC subset patterns distinguishing individuals with MDD from HC. Multivariate linear regression revealed a significant predictive contribution of cytokine-producing DCs, together with age and BMI, in females but not in males.DiscussionThese findings demonstrate sex-specific alterations in cytokine-producing DCs in MDD and a strong association between IL-23+ cDCs and depressive symptom severity, suggesting a key role for these cells in immune dysregulation, particularly in females with depression.